KONSEP TUJUAN HIDUP MANUSIA DALAM PERSPEKTIF AL-QUR’AN - Ibrahim, Arfah (Prodi Ilmu Al-Qur'an dan Tafsir, 2023)
This article aims to discuss the concept of the purpose of human life from the perspective of the Qur'an, how humans were created and the function of humans as caliphs on this earth in carrying out the mandate from Allah swt. while on the surface of the earth. Humans were created in the best form with various advantages given that they can adapt, are able to choose good paths and bad ones so as not to lead them down a path that will destroy them. Apart from that, humans are creatures that can be educated so that with this potential humans can be educated in a direction that is in accordance with Islamic teachings. The purpose and benefit of knowing the concept of humans in the Qur'an is to know the various strengths and advantages that humans have so that by knowing the conditions and potential they have, humans can find out the ideal method for developing the potential that humans have so that they can lead the world in development. civilization in the direction prescribed in the Qur'an and al-Hadith.